Blackened copper foil, blackening solution and surface treatment method

By using a blackening liquid containing ferrous sulfate to blacken the copper foil, a densely distributed structure of nano-scale particles is formed, which solves the problem of the inability to take into account both the roughness and the peel strength of the blackening copper foil product, and achieves a good balance of performance with low surface roughness, high peel strength and corrosion resistance of the coating.

CN119736679APending Publication Date: 2025-04-01CHINALCO RES INST OF SCI & TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411822423.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the roughness and peel resistance strength of the blackened copper foil product cannot be taken into account, and it is difficult to achieve a lower roughness while meeting the high peel resistance strength.

Method used

The blackening liquid containing 100-140g/L sulfuric acid, 25-45g/L copper sulfate, 5-15ppm chloride ions, 2-4g/L ferrous sulfate, 4-8g/L zinc sulfate and 6-10g/L nickel sulfate was used to blackening the copper foil. Through co-deposition of ferrous ions with Cu2+, Ni2+, and Zn2+, a dense distribution structure of nano-scale particles was formed, and the coordinated control of blackening effect, surface roughness and anti-peel strength was achieved.

Benefits of technology

The performance balance of surface roughness and peel strength of blackened copper foil products is significantly improved, ensuring the corrosion resistance and oxidation resistance of the coating, while avoiding the use of harmful substances such as arsenic, lead, mercury, cobalt, cadmium and thiocyanide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736679A_ABST
    Figure CN119736679A_ABST
Patent Text Reader

Abstract

The present invention relates to a blackened copper foil, a blackening liquid and a surface treatment method. The blackening liquid used for the blackened copper foil of the present invention comprises: 100-140 g / L sulfuric acid, 25-45 g / L copper sulfate, 5-15 ppm chloride ions, 2-4 g / L ferrous sulfate, 4-8 g / L zinc sulfate and 6-10 g / L nickel sulfate. The surface treatment method for the blackened copper foil of the present invention comprises the step of performing a blackening treatment on the copper foil, and the blackening treatment uses the above-mentioned blackening liquid. The present invention can improve the performance balance between the surface roughness and the peeling strength of the blackened copper foil product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copper foil surface treatment, and more specifically to a blackening liquid for blackening copper foil, a surface treatment method for blackening copper foil using the blackening liquid, and a blackened copper foil product prepared by the method. Background Art

[0002] Printed circuit boards, also known as PCB circuit boards, are essential accessories in modern electronic devices. They are widely used in communications, digital products, instrumentation, medical equipment, aerospace, military industries and other fields. At present, as PCB is developing towards multi-layer, thin, high-density and high-speed, copper foil, as a key conductive material in printed circuit boards, is also developing towards high-quality performance such as thinness, high bending resistance, low profile, high ductility and high peeling resistance. The performance of copper foil is closely related to its surface treatment. Whether it is electrolytic copper foil or rolled copper foil, it must undergo surface treatment before being made into copper-clad boards. The surface treatment process of copper foil mainly includes: pretreatment, roughening and curing treatment, barrier layer plating treatment, surface passivation and silane coupling agent treatment, drying and other steps.

[0003] In recent years, the gradual popularization of advanced electronic information technology represented by high-speed servers and 5G communications has effectively promoted the rapid development of the PCB industry. Thinning and high integration have gradually become the mainstream trend of high-frequency and high-speed PCB development. With the reduction of the thickness of the dielectric layer of the PCB board and the increase of the glass transition temperature, high-frequency and high-speed PCBs have put forward higher requirements for the copper foil of electronic circuits. For PCBs with copper foil as the signal transmission carrier, the skin depth (δs) is mainly affected by the signal frequency (f). The higher the signal frequency f, the smaller the skin depth δs, and the more the current is concentrated in the surface area of ​​the line. When the temperature is 20℃ and the frequency is 1GHz, the skin depth δs of copper is 2.09μm; when the signal frequency f reaches 10GHz, the skin depth δs of copper is only 0.66μm. The roughness of ordinary electrolytic copper foil is about 5.0μm, and 5G signals are basically transmitted in the rough layer of copper foil. The uneven distribution of current in the line will cause the resistance to increase. The increase in resistance will cause the high-frequency signal transmitted in the copper foil to be dissipated in the form of heat energy. The proportion increases, which ultimately leads to more serious attenuation of the signal. Therefore, in order to ensure the integrity of signal transmission, the adverse effects of skin effect on signal transmission must be minimized. Therefore, high-speed and high-frequency PCBs that are sensitive to signal transmission loss require the copper foil of electronic circuits to have a lower roughness Rz.

[0004] As electronic devices develop towards high performance and miniaturization, printed circuits are also rapidly developing towards high density and multi-layering, increasing the demand for inner surface treated copper foil. The inner copper foil used as a printed circuit board must not only be bonded to the resin substrate on its rough surface, but also on its smooth surface. However, since the smooth surface of ordinary copper foil is relatively smooth and the bonding strength with the resin substrate is insufficient, excessive roughness on the surface of the copper foil will increase impedance, affect signal transmission, and increase the risk of short circuit. How to improve the bonding strength between the smooth surface of the copper foil and the resin substrate while ensuring the performance of the smooth surface and prevent the copper foil from cracking is an urgent problem to be solved.

[0005] PCB is made of resin substrate and copper foil by laminating to form a "sandwich" structure and then hot pressing. Generally, the thinner the copper foil, the lower the roughness. When the roughness is low, there are fewer mechanical riveting points between the copper foil and the resin substrate at the microscopic level, resulting in low adhesion (anti-peel strength) at the interface between the copper foil and the resin substrate at the macroscopic level. This may cause risks and hidden dangers of board explosion in downstream PCB drilling or reflow soldering processes, so the anti-peel strength of copper foil is a key point that the copper foil industry and downstream customers are very concerned about.

[0006] The peel strength of copper foil is quantified according to IPC-TM 650 2.4.8C. According to elastic theory, the factor affecting mechanical adhesion P is the tensile strength of the resin σ N , the ratio of the copper foil modulus E to the resin modulus Y, the thickness of the deformed resin y o , copper foil thickness δ. From the formula, it can be seen that "mechanical adhesion P" is positively correlated with "copper foil thickness δ". The thinner the copper foil, the smaller its P value will be.

[0007]

[0008] During the hot pressing process, the thickness of the deformed resin is directly related to the roughness of the copper foil. Generally speaking, the increase in the roughness of the copper foil is conducive to improving the peel strength, but high roughness will cause the following problems: 1) When the distance between two copper conductors is too narrow, there may be a risk of short circuit between adjacent conductors due to residual copper. As the thickness of the resin substrate becomes thinner and thinner, when the roughness of the copper foil is larger, it may pierce the substrate and cause the upper and lower layers of copper foil to be connected and short-circuited. 2) In high-frequency and high-speed circuits, there is a phenomenon called "skin effect", that is, when the frequency of the transmitted signal is higher, the current is more concentrated on the outer layer of the conductor, the "skin effect" is more obvious, and the greater the roughness of the copper foil, the higher the conductor loss. Therefore, copper foil with high roughness will cause increased signal attenuation or even distortion.

[0009] In summary, copper foil suitable for high-frequency and high-speed circuit boards needs to be designed with a suitable roughness in order to establish a balance between anti-peeling performance and signal transmission performance. However, the roughness of copper foil of a few microns or dozens of microns is low, and naturally encounters a bottleneck in improving the anti-peeling strength, which will also bring disadvantages and challenges to the development of related industries. Therefore, in-depth research and development of copper foil products to change the microscopic morphology of copper nodules without significantly changing the roughness so that they have a larger specific surface area, thereby providing more mechanical riveting force and thus improving the anti-peeling strength is one of the problems that need to be solved urgently. This is of great significance to promoting the development of the high-end copper clad laminate industry, especially the current high-end copper clad laminate or FPC board for 5G communications.

[0010] Copper foil is mainly divided into electrolytic copper foil and rolled copper foil according to different preparation processes, both of which can be used for flexible printed circuit boards. In order to meet the requirements of circuit boards for the heat resistance and corrosion resistance of copper foil, the surface of copper foil generally needs to be blackened. Blackened foil is a process technology for blackening the surface of rolled copper foil when it is used in high-end flexible printed circuit boards (FPC) to achieve the performance requirements of peel strength, corrosion resistance, high-temperature oxidation resistance, etc. This technology was previously mastered by only a very small number of Japanese companies. In recent years, in the related projects and scientific papers on "Research and Development of Blackened Rolled Copper Foil for Flexible Printed Circuit Boards", the morphology of the copper foil substrate, solution concentration, temperature, pH, type and content of additives, current density, etc. that affect the blackening effect have been studied in depth, and technical problems such as liquid ratio, color chromaticity, surface color difference, and severe powder loss have been overcome one after another.

[0011] For the blackening treatment of copper foil, the traditional surface treatment process includes: chemical degreasing, pickling, roughening, curing, pickling, nickel plating, zinc plating, chrome plating, silane coupling agent coating, drying and other steps. The chromium plating process uses a chromium-containing plating solution. The compounds formed by the element generally have great harm to the environment and human body. The toxicity of chromium is related to its valence state. Hexavalent chromium is 100 times more toxic than trivalent chromium, and is easily absorbed by the human body and accumulates in the body. Trivalent chromium and hexavalent chromium can be converted into each other, which is harmful to the human respiratory tract, digestive system, eyes, ears, mouth and nose, such as chromium skin ulcers, chromium dermatitis and eczema, chromium rhinitis, and even cause whole body paralysis in severe cases. At the same time, a large number of chromium-containing compounds produced in industrial production are also an important source of environmental pollution. For this reason, the study of chromium-free blackening plating solution and its process has become an urgent problem that the industry needs to solve.

[0012] In the domestic blackened copper foil production process, cyanide black nickel plating technology is also used. Cyanide electroplating seriously pollutes the environment. The plating solution is difficult to handle and discharge. Cyanide is highly toxic and has serious harm to the human body. In addition, the plating solution contains a large amount of cadmium compounds, which are very harmful to the human body and the environment.

[0013] At present, the blackening treatment of copper foil surface is mainly carried out by nickel-cobalt electroplating, and a blackening agent is added to the electroplating solution of nickel-cobalt electroplating. Generally, thiocyanate such as KSCN, NHSCN, SC(NH)2 is used as a blackening agent to obtain a better black effect, but thiocyanate will cause serious pollution problems. Therefore, the pollution caused by using thiocyanate as a blackening agent in the blackening process of copper foil is another problem that needs to be solved urgently.

[0014] Chinese patent CN102618902B discloses a surface treatment process for copper foil for flexible copper clad laminates. In the blackening step, a blackening agent is added, wherein the blackening agent is selected from ammonium citrate, ammonium sulfate, ammonia water, ammonium thiocyanate, and thiourea, to form a black ultra-fine coating on the surface of the copper foil that can improve the corrosion resistance and etching properties of the copper foil. Chinese patent CN105603480 B discloses a black surface treatment method for rolled copper foil. The copper foil is subjected to degreasing treatment, primary roughening, secondary roughening, tertiary roughening, nickel-cobalt alloy treatment, galvanizing treatment, and then rust-proof treatment and coating with a layer of silane coupling agent to finally obtain the product. The blackening method provided by Chinese patent CN116377529A is to place the copper foil in a blackening solution for electroplating. The electroplating conditions are: the current density is 5 to 15 A / dm 2 , the electroplating time is 5 to 12 seconds, and the temperature is 30 to 45°C; the components of the blackening liquid include: 25 to 50 g / L zinc sulfate, 10 to 25 g / L sodium citrate, 10 to 20 g / L boric acid, 15 to 25 g / L ammonium sulfate, 5 to 15 g / L polyacrylamide, and 4 to 8 g / L gelatin. The invention forms an optical trap on the surface of the copper foil by the combined action of polyacrylamide and gelatin. When light is irradiated on the surface of the copper foil, multiple reflections and refractions occur, thereby achieving the purpose of blackening. Chinese patent CN105002496 A provides a blackening liquid mixed with potassium pyrophosphate (K4P2O7), nickel sulfate, zinc sulfate, additive A, additive B, a complexing agent and other substances. CN 112501659A provides a cyanide-free nickel electroplating blackening process for rolled copper foil and a matching blackening plating solution, wherein the blackening plating solution includes nickel sulfate and nickel chloride, sodium citrate, ammonium sulfate, boric acid, sodium ethylenediaminetetraacetate and sodium polyacrylate. Chinese patent CN112609217A discloses a blackening solution and a cyanide-free zinc-plating and cadmium-free electroplating blackening process, wherein the components include zinc sulfate, zinc chloride, potassium pyrophosphate, sodium ethylenediaminetetraacetate, boric acid, didodecyldimethylammonium chloride, didodecyldimethylammonium bromide and a surfactant additive.

[0015] In summary, the existing technology of blackened copper foil has the problem that both the roughness and peel strength of the blackened copper foil product cannot be taken into account. Therefore, the art is in urgent need of developing a blackening liquid and a surface treatment method to obtain a good balance between lower roughness and higher peel strength. Summary of the invention

[0016] The purpose of the present disclosure is to provide a blackening liquid for blackening copper foil, a surface treatment method for blackening copper foil using the blackening liquid, and a blackened copper foil product prepared by the method, so as to solve the problem that both the roughness and the peeling resistance of the blackened copper foil product in the prior art cannot be taken into account.

[0017] In order to achieve the above-mentioned purpose, according to the first aspect of the present disclosure, a blackening liquid for blackening copper foil is provided, which comprises: 100-140 g / L sulfuric acid, 25-45 g / L copper sulfate, 5-15 ppm chloride ion, 2-4 g / L ferrous sulfate, 4-8 g / L zinc sulfate and 6-10 g / L nickel sulfate.

[0018] Furthermore, the blackening liquid also includes 80 to 120 ppm of collagen.

[0019] Furthermore, the blackening solution does not include arsenic, lead, mercury, cobalt, cadmium and thiocyanate.

[0020] According to a second aspect of the present disclosure, a surface treatment method for blackening copper foil is provided, the method comprising the step of performing a blackening treatment on the copper foil, wherein the blackening treatment uses the blackening liquid described in the first aspect of the present invention.

[0021] Further, the method comprises the following steps: step S1: degreasing the copper foil raw material to obtain degreased copper foil; step S2: pickling the degreased copper foil to obtain pickled copper foil; step S3: performing secondary roughening-curing treatment on the pickled copper foil to obtain secondary roughening-cured copper foil; the secondary roughening-curing treatment comprises sequentially performing a first roughening treatment, a first curing treatment, a second roughening treatment, and a second curing treatment on the pickled copper foil; the first curing treatment and the second curing treatment comprise curing electrodeposition treatment using a curing liquid, the curing liquid comprising: 100-140 g / L sulfuric acid, 30-60 g / L copper sulfate, 8-12 ppm chloride ions, and 5-15 ppm collagen; step S4: placing the secondary roughening-cured copper foil in a blackening liquid for electrodeposition treatment to obtain a blackened copper foil, the conditions of the electrodeposition treatment being: a current density of 28-40 A / dm 2 , electrodeposition time 4 to 8 s, temperature 30 to 45° C.; Step S5: performing silane coupling treatment on the blackened copper foil to obtain a copper foil product.

[0022] Furthermore, the degreasing treatment in step S1 includes placing the copper foil raw material in an alkaline solution for electrolytic degreasing; the alkaline solution contains: 30-50 g / L sodium hydroxide and 15-30 g / L sodium carbonate; the conditions for the electrolytic degreasing are: current density 4-6 A / dm 2 , temperature 20-40°C, degreasing time 12-18s; the electrolytic degreasing is preferably carried out twice.

[0023] Furthermore, the pickling treatment in step S2 includes placing the degreased copper foil in an acid solution for pickling; the acid solution contains 100 to 150 g / L of sulfuric acid; and the pickling conditions are: a temperature of 20 to 40° C. and a pickling time of 12 to 18 seconds.

[0024] Further, in step S3, the first roughening treatment includes: placing the pickled copper foil in a roughening solution for roughening electrodeposition treatment to obtain a first roughened copper foil; the first curing treatment includes: placing the first roughened copper foil in a curing solution for curing electrodeposition treatment to obtain a first cured copper foil; the second roughening treatment includes: placing the first cured copper foil in a roughening solution for roughening electrodeposition treatment to obtain a second roughened copper foil; the second curing treatment includes: placing the second roughened copper foil in a curing solution for curing electrodeposition treatment to obtain a secondary roughening-cured copper foil; the roughening solution contains: 100-140 g / L sulfuric acid, 10-30 g / L copper sulfate, and 0.3-1.5 ppm chloride ions; the conditions for the roughening electrodeposition treatment are: a current density of 8-12 A / dm 2 , electrodeposition time 4 to 8 s, temperature 20 to 40 ° C; curing electrodeposition treatment conditions: current density 30 to 50 A / dm 2 , electrodeposition time 4 to 8 s, temperature 20 to 40°C.

[0025] Further, step S5 includes: spraying the blackened copper foil with an aqueous solution of a silane coupling agent at a temperature of 25 to 45° C., and then drying at a temperature of 180 to 280° C. for 6 to 8 seconds to obtain the copper foil product; the mass concentration of the silane coupling agent in the aqueous solution is 0.5 to 3%; the silane coupling agent is selected from one or more of anilinemethyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, glyceraldehydepropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-(isobutyleneoxy)propyltrimethoxysilane, and (3-chloropropyl)trimethoxysilane.

[0026] According to a third aspect of the present disclosure, there is provided a blackened copper foil product produced by the surface treatment method described in the second aspect of the present invention.

[0027] As described above, the blackened copper foil product prepared by the known technology has the problem that both roughness and peel strength cannot be taken into account. In particular, it is often difficult to achieve a lower roughness when a higher peel strength is satisfied. The present invention uses a blackening solution to which ferrous sulfate is added in the blackening stage, that is, a blackening solution containing 100-140 g / L sulfuric acid, 25-45 g / L copper sulfate, 5-15 ppm chloride ions, 2-4 g / L ferrous sulfate, 4-8 g / L zinc sulfate and 6-10 g / L nickel sulfate. The blackening electrodeposition process of the copper foil can be improved. At the same time, the ferrous ions are combined with Cu 2+ 、Ni 2+ 、Zn 2+ The co-deposition effect can form a structure with dense distribution of nano-scale particles on the surface and staggered accumulation of multiple nano-scale particles at height, which can achieve coordinated control of blackening effect, surface roughness and anti-peel strength performance, and finally achieve a good performance balance between surface roughness and anti-peel strength of blackened copper foil products.

[0028] Therefore, compared with the prior art, the technical solution disclosed in the present invention can significantly improve the performance balance between the surface roughness and the peeling strength of the blackened copper foil product. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0030] Figure 1 The microstructure morphology of the blackened copper foil prepared according to one embodiment of the present invention is shown. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with specific implementation methods. The embodiments shown below do not limit the invention content recorded in the claims. It should be noted that the embodiments and features in the embodiments in this application can be combined with each other without conflict.

[0032] In view of the deficiencies in the prior art mentioned in the background technology, a specific embodiment of the present disclosure provides a blackening liquid for blackening copper foil, which comprises: 100-140 g / L sulfuric acid, 25-45 g / L copper sulfate, 5-15 ppm chloride ions, 2-4 g / L ferrous sulfate, 4-8 g / L zinc sulfate and 6-10 g / L nickel sulfate.

[0033] The present invention can improve the blackening electrodeposition process of copper foil by adding ferrous sulfate to the blackening solution. 2+ 、Ni 2+ 、Zn2+ The co-deposition effect can form a structure with dense distribution of nano-scale particles on the surface and staggered accumulation of multiple nano-scale particles at height, which can achieve coordinated control of blackening effect, surface roughness and anti-peel strength performance, and finally achieve a good performance balance between surface roughness and anti-peel strength of blackened copper foil products.

[0034] Furthermore, since the blackening liquid of the present invention contains copper, zinc, nickel and iron elements, the blackening layer of the blackened copper foil product will also contain copper, zinc, nickel and iron elements at the same time, thereby ensuring the corrosion resistance and oxidation resistance of the coating, eliminating the chromium plating passivation step and shortening the process flow.

[0035] Ferrous sulfate is preferably added to the blackening solution in the form of ferrous sulfate heptahydrate.

[0036] In the blackening liquid, the content of sulfuric acid is preferably 100 to 130 g / L, and more preferably 110 to 120 g / L.

[0037] In the blackening solution, the content of copper sulfate is preferably 25 to 40 g / L, and more preferably 30 to 35 g / L.

[0038] In the blackening liquid, the content of chloride ions is preferably 5 to 12 ppm, and more preferably 5 to 10 ppm.

[0039] In the blackening liquid, the content of ferrous sulfate is preferably 2 to 3 g / L, and more preferably 2.5 to 3 g / L.

[0040] In the blackening solution, the content of zinc sulfate is preferably 4 to 7 g / L, and more preferably 4 to 6 g / L.

[0041] In the blackening solution, the content of nickel sulfate is preferably 6 to 9 g / L, and more preferably 6 to 8 g / L.

[0042] Preferably, the blackening solution of the present invention may also include 80 to 120 ppm of collagen. The addition of a positively charged leveling agent (collagen) to the blackening solution can promote electrochemical deposition at the pits of the pre-treated polished surface while inhibiting electrochemical deposition at the protrusions, thereby reducing the roughness of the blackened surface while ensuring an increase in the specific surface area, thereby obtaining a blackened copper foil product with a further improved balance between roughness and anti-peel strength.

[0043] By using the above-mentioned blackening liquid, the present invention can achieve blackening treatment on the surface of the copper foil and obtain a blackened copper foil with excellent performance. The blackening liquid of the present invention does not contain arsenic, lead, mercury, cobalt, cadmium and thiocyanate. Since arsenic, lead, mercury, cobalt, cadmium and thiocyanate and other substances that pollute the environment are not used in the blackening process, the present invention is conducive to protecting the environment.

[0044] Another specific embodiment of the present invention provides a surface treatment method for blackening copper foil, which includes using the blackening solution of the present invention to blacken the copper foil. The present invention can improve the blackening electrodeposition process of the copper foil by using a blackening solution to which ferrous sulfate is added during the blackening stage, that is, a blackening solution containing 100-140 g / L sulfuric acid, 25-45 g / L copper sulfate, 5-15 ppm chloride ions, 2-4 g / L ferrous sulfate, 4-8 g / L zinc sulfate, and 6-10 g / L nickel sulfate. At the same time, the ferrous ions combine with Cu 2+ 、Ni 2+ 、Zn 2+ The co-deposition effect can form a structure with dense distribution of nano-scale particles on the surface and staggered accumulation of multiple nano-scale particles at height, which can achieve coordinated control of blackening effect, surface roughness and anti-peel strength performance, and finally achieve a good performance balance between surface roughness and anti-peel strength of blackened copper foil products.

[0045] In addition, the present invention forms a co-deposition layer of copper, zinc, nickel and iron on the surface of the copper foil, thereby realizing a blackening treatment of the surface of the copper foil. During the blackening process, no environmentally polluting substances such as arsenic, lead, mercury, cobalt, cadmium and thiocyanate are used, which is beneficial to protecting the environment. At the same time, because the blackening layer contains copper, zinc, nickel and iron elements at the same time, the corrosion resistance and oxidation resistance of the coating are guaranteed, the chromium plating passivation process is omitted, and the process flow is shortened.

[0046] In a specific embodiment, the surface treatment method of the present invention comprises the following steps: step S1: degreasing the copper foil raw material to obtain degreased copper foil; step S2: pickling the degreased copper foil to obtain pickled copper foil; step S3: performing secondary roughening-curing treatment on the pickled copper foil to obtain secondary roughening-cured copper foil; the secondary roughening-curing treatment comprises sequentially performing a first roughening treatment, a first curing treatment, a second roughening treatment, and a second curing treatment on the pickled copper foil; the first curing treatment and the second curing treatment comprise curing electrodeposition treatment using a curing liquid, the curing liquid comprising: 100-140 g / L sulfuric acid, 30-60 g / L copper sulfate, 8-12 ppm chloride ions, and 5-15 ppm collagen; step S4: placing the secondary roughening-cured copper foil in a blackening liquid for electrodeposition treatment to obtain a blackened copper foil, and the conditions of the electrodeposition treatment are: a current density of 28-40 A / dm 2 , electrodeposition time 4 to 8 s, temperature 30 to 45° C.; Step S5: performing silane coupling treatment on the blackened copper foil to obtain a copper foil product.

[0047] By using a curing liquid with collagen added in the curing stage, the chloride ions can be selectively adsorbed on the (220) surface and the growth of the surface can be promoted. At the same time, collagen is selectively adsorbed on the (111) surface and the lateral growth of the precipitate is inhibited, so that particles with an acute pyramidal shape can be obtained. The combined effect of the two forms a nearly spherical curing layer of about 100 nm. The present invention can further reduce the roughness of the copper foil product and improve the oxidation resistance by using a curing liquid with collagen added in the curing stage for curing electrodeposition treatment.

[0048] In one embodiment, the degreasing treatment in step S1 includes placing the copper foil raw material in an alkali solution for electrolytic degreasing; the alkali solution contains: 30-50 g / L sodium hydroxide and 15-30 g / L sodium carbonate; the conditions for the electrolytic degreasing are: current density 4-6 A / dm 2 , temperature 20-40°C, degreasing time 12-18s; the electrolytic degreasing is preferably carried out twice.

[0049] Degreasing (or degreasing) is the process of removing organic pollutants from the surface of copper foil, such as grease, oil, wax, dust, etc. These pollutants may adhere to the surface during the production, transportation or storage of copper foil. The presence of pollutants may affect the direct contact between the processing solution (such as the roughening solution, curing solution and blackening solution in the subsequent stage) and the copper foil, which may affect the smooth progress of the chemical reaction to a certain extent, resulting in uneven formation of the curing layer, blackening layer, etc., thereby affecting the performance of the copper foil product and the manufacturing quality of the PCB. The above-mentioned degreasing treatment can help remove these pollutants, prevent pollutants from affecting the subsequent copper foil processing, and obtain high-quality copper foil products. Degreasing treatment can remove pollutants by electrochemical or chemical immersion cleaning.

[0050] The present invention preferably adopts electrolytic degreasing treatment. By using the above-mentioned alkali solution and carrying out the treatment under the above-mentioned electrolytic degreasing conditions, degreased copper foil can be obtained more efficiently.

[0051] The concentration of the alkali solution is preferably 30-45 g / L sodium hydroxide and 20-30 g / L sodium carbonate, and more preferably 35-40 g / L sodium hydroxide and 20-25 g / L sodium carbonate; the current density of the electrolytic degreasing is preferably 4-5 A / dm 2 The degreasing time is preferably 12 to 15 seconds, more preferably 13 to 14 seconds; the degreasing temperature is preferably 20 to 35°C, more preferably 25 to 35°C.

[0052] Electrolytic degreasing can be performed once or multiple times. The present invention preferably performs electrolytic degreasing twice, which can improve the processing efficiency and obtain a better degreasing effect. More preferably, the two electrolytic degreasing of the copper foil can be performed in a dynamic continuous manner, thereby further improving the processing efficiency and shortening the entire processing flow.

[0053] In a specific embodiment, the pickling treatment in step S2 includes placing the degreased copper foil in an acid solution for pickling; the acid solution contains 100-150 g / L of sulfuric acid; the pickling conditions are: temperature 20-40° C., pickling time 12-18 s.

[0054] Pickling is the chemical cleaning of the copper foil surface by acidic solution (such as sulfuric acid) to remove oxides, metal debris, residual alkaline substances or other inorganic pollutants. During the production process of copper foil, the copper foil surface may form an oxide layer or be contaminated by other inorganic pollutants, which will affect the bonding effect and reactivity of subsequent treatments. Pickling can activate the copper foil surface, making it cleaner and more active, creating good conditions for subsequent roughening and curing treatments, and ensuring the uniformity and quality of the coating.

[0055] The pickling time is preferably 12 to 16 seconds, more preferably 12 to 14 seconds; the concentration of sulfuric acid is preferably 100 to 140 g / L, more preferably 100 to 130 g / L; the pickling temperature is preferably 20 to 35°C, more preferably 25 to 35°C.

[0056] In a specific embodiment, in step S3, the first roughening treatment includes: placing the pickled copper foil in a roughening solution for roughening electrodeposition treatment to obtain a first roughened copper foil; the first curing treatment includes: placing the first roughened copper foil in a curing solution for curing electrodeposition treatment to obtain a first cured copper foil; the second roughening treatment includes: placing the first cured copper foil in a roughening solution for roughening electrodeposition treatment to obtain a second roughened copper foil; the second curing treatment includes: placing the second roughened copper foil in a curing solution for curing electrodeposition treatment to obtain a secondary roughening-cured copper foil; the roughening solution contains: 100-140 g / L sulfuric acid, 10-30 g / L copper sulfate, and 0.3-1.5 ppm chloride ions; the conditions for the roughening electrodeposition treatment are: current density 8-12 A / dm 2 , electrodeposition time 4 to 8 s, temperature 20 to 40 ° C; curing electrodeposition treatment conditions: current density 30 to 50 A / dm 2 , electrodeposition time 4 to 8 s, temperature 20 to 40°C.

[0057] The roughening and curing process of copper foil is an important step in the surface treatment of copper foil in the manufacture of printed circuit boards (PCBs). It is mainly used to improve the bonding strength between the copper foil and the substrate, and adjust the microstructure of the copper foil surface to meet the performance requirements of the circuit board, such as improving the peeling strength, improving the solderability, and enhancing the conductivity.

[0058] The purpose of the roughening process is to form a microscopic rough structure on the surface of the copper foil, increase the specific surface area of ​​the copper foil, and thus improve its bonding strength with the resin substrate. In the PCB industry, this process is usually carried out by electrochemical methods, that is, under specific current density, temperature and time conditions, the copper foil is used as a cathode and immersed in a solution containing specific metal ions (such as copper sulfate) and chloride ions. Chloride ions can play an important role in the roughening process. It can help copper ions to selectively deposit on the surface of the copper foil to form pyramid-shaped or other microstructured copper particles. These microstructured copper particles can penetrate into the micropores of the resin substrate to form a mechanical riveting effect, thereby increasing the bonding strength between the copper foil and the substrate. The control of the roughening process is also important. Too high a current density or too long a processing time will cause the surface to be excessively rough, thereby affecting subsequent processes such as welding and signal transmission performance.

[0059] In the above specific embodiment of the present invention, by adjusting the chloride ions and the current density, the copper particle roughening layer can be formed by rapid electrodeposition. In the first roughening treatment and the second roughening treatment, the same or slightly different roughening solutions can be used, and the same or slightly different roughening electrodeposition treatment conditions can be used. The current density is preferably 8 to 11 A / dm 2 , more preferably 8 to 10 A / dm 2 ; The electrodeposition time is preferably 4 to 7 seconds, more preferably 4 to 6 seconds; The temperature is preferably 20 to 35°C, more preferably 25 to 35°C. In the roughening solution, the content of sulfuric acid is preferably 100 to 130 g / L, more preferably 100 to 120 g / L; the content of copper sulfate is preferably 10 to 25 g / L, more preferably 10 to 20 g / L; The content of chloride ions is preferably 0.3 to 1.2 ppm, more preferably 0.5 to 1.0 ppm.

[0060] The curing process is an important step after roughening, which aims to further adjust and stabilize the microstructure of the copper foil surface, while improving the surface hardness and wear resistance. This process is usually carried out by electrodeposition, and the copper foil is immersed in the curing liquid again as the cathode. The conditions of the curing process (such as current density, time, temperature, etc.) can be carefully controlled to ensure that the final copper foil product has excellent performance.

[0061] In the first curing treatment and the second curing treatment of the present invention, the same or slightly different curing liquids may be used, and the same or slightly different curing electrodeposition treatment conditions may be used. The current density is preferably 30 to 45 A / dm 2 , more preferably 30 to 40 A / dm 2 ; The electrodeposition time is preferably 4 to 7 seconds, more preferably 4 to 6 seconds; The temperature is preferably 20 to 35°C, more preferably 25 to 35°C. In the curing solution, the content of sulfuric acid is preferably 100 to 130 g / L, more preferably 100 to 120 g / L; the content of copper sulfate is preferably 30 to 55 g / L, more preferably 30 to 50 g / L; the content of chloride ions is preferably 8 to 11 ppm, more preferably 9 to 10 ppm; the content of collagen is preferably 5 to 12 ppm, more preferably 5 to 10 ppm of collagen.

[0062] In a specific embodiment, step S5 includes: spraying blackened copper foil with an aqueous solution of a silane coupling agent at a temperature of 25 to 45° C., and then drying at a temperature of 180 to 280° C. for 6 to 8 seconds to obtain the copper foil product; the mass concentration of the silane coupling agent in the aqueous solution is 0.5 to 3%; the silane coupling agent is selected from one or more of anilinemethyltriethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, glyceraldehydepropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-(isobutyleneoxy)propyltrimethoxysilane, and (3-chloropropyl)trimethoxysilane.

[0063] Silane coupling agent treatment is a surface modification technology that is widely used to enhance the interface between metal materials and organic polymer materials, and is particularly useful for improving the bonding between copper foil and resin substrates, thereby improving the reliability and durability of PCBs. Silane coupling agents are a class of compounds containing silane groups and organic functional groups. Silane groups can form chemical bonds on metal surfaces (such as copper), while organic functional groups can form chemical bonds or physical interactions with organic resins, such as hydrogen bonds or hydrophobic interactions. This dual-functional property enables silane coupling agents to act as a "bridge" between two different materials, enhancing the bonding between them.

[0064] In a specific embodiment of the present invention, during the spraying of the silane coupling agent, the concentration of the silane coupling agent is preferably 0.5-2%, more preferably 0.5-1.5%; the spraying temperature is preferably 25-40°C, more preferably 25-35°C; the subsequent drying temperature is preferably 190-260°C, more preferably 200-240°C; the drying time is 6-8s, preferably 7s.

[0065] The silane coupling agent is preferably one or two of 3-aminopropyltriethoxysilane, (3-chloropropyl)trimethoxysilane, anilinomethyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane and 3-glycidyloxypropyltrimethoxysilane.

[0066] The blackening liquid, roughening liquid, curing liquid, alkali liquid, and acid liquid of the present invention preferably use water as a solvent.

[0067] The chloride ions in the blackening solution, roughening solution and solidifying solution of the present invention can be added in the form of hydrochloric acid or chloride salts, such as CuCl2, HCl, preferably HCl.

[0068] According to another embodiment of the present invention, a blackened copper foil product prepared by the surface treatment method of the present invention is provided. The blackened copper foil product has a good performance balance in terms of surface roughness and peeling strength.

[0069] In a preferred embodiment, compared with the prior art, the present invention has high peel strength, low surface roughness, and good anti-oxidation performance, and its significant beneficial effects are mainly reflected in the following aspects:

[0070] (1) In the coarsening stage, the chloride ions and current density are adjusted to form a copper particle coarsening layer by rapid electrodeposition. In the curing stage, collagen is added to promote the selective adsorption of chloride ions on the (220) surface and promote the growth of the surface. At the same time, collagen is selectively adsorbed on the (111) surface and inhibits the lateral growth of the precipitate, so that particles with sharp pyramidal morphology can be obtained. The combined effect of the two forms a nearly spherical solidified layer of about 100 nm. In the blackening stage, ferrous sulfate is further added to improve the electrodeposition process, and then combined with Cu 2+ 、Ni 2+ 、Zn 2+ The effect of co-deposition ultimately forms a structure in which nanoscale particles are densely distributed on the surface and multiple nanoscale particles are staggered and stacked at height, and ultimately achieves the coordinated control of blackening effect, surface roughness and anti-peel strength performance.

[0071] (2) A positively charged leveling agent (collagen) is added to the blackening liquid to promote electrochemical deposition at the pits of the pre-treated polished surface while inhibiting electrochemical deposition at the protrusions, thereby reducing the roughness of the blackened surface while ensuring the specific surface area.

[0072] (3) The blackened foil formed by the present invention has a single nearly spherical particle size on the coating of hundreds of nanometers, and the nearly spherical particles are flatly stacked in a specific area on the surface of the foil, and more than 95% of the stacking height in the thickness direction is less than 1 μm. This staggered and well-organized structure simultaneously ensures high density, low roughness, high peel strength, and bright and dark L value (black) of the coating, achieving an excellent balance of performance.

[0073] (4) The present invention performs a co-deposition layer of copper, zinc, nickel and iron on the surface of the copper foil after roughening and curing, thereby achieving a blackening treatment on the surface of the copper foil. During the blackening process, no environmentally polluting substances such as arsenic, lead, mercury, cobalt, cadmium and thiocyanate are used, which is beneficial to environmental protection. Since the blackening layer contains copper, zinc, nickel and iron elements at the same time, the corrosion resistance and oxidation resistance of the coating are guaranteed, the chromium plating passivation process is omitted, and the process flow is shortened.

[0074] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0075] Example 1

[0076] Degreasing: The copper foil is alkaline washed with an aqueous solution of 30 g / L sodium hydroxide and 15 g / L sodium carbonate. The current density of the alkaline washing is 4 A / dm 2 , the cleaning time is 12s, the temperature is 40℃, and the alkaline cleaning is performed twice;

[0077] Pickling: The copper foil was pickled with a 100 g / L sulfuric acid aqueous solution for 18 s at a temperature of 30 °C.

[0078] Roughening I: The pickled copper foil is placed in a roughening solution for electrodeposition treatment; wherein the roughening solution uses water as a solvent, and its components include: 100g / L sulfuric acid, 30g / L copper sulfate, and 1.5ppm chloride ions; the electrodeposition conditions are: the current density is 11A / dm 2 , the electrodeposition time is 4s, and the temperature is 30°C;

[0079] Curing I: The roughened copper foil is placed in a curing solution for electrodeposition treatment; wherein the curing solution uses water as a solvent, and its components include: 100g / L sulfuric acid, 60g / L copper sulfate, 12ppm chloride ions, and 13ppm collagen; the electrodeposition conditions are: the current density is 50A / dm 2 , the electrodeposition time was 4 s and the temperature was 35 °C;

[0080] Repeat the above steps to perform roughening II treatment; repeat the above steps to perform curing II treatment;

[0081] Blackening: Place the cured copper foil in a blackening solution for electrodeposition treatment; the blackening solution uses water as a solvent and its components include: 130g / L sulfuric acid, 25g / L copper sulfate, 8ppm chloride ion, 2g / L ferrous sulfate, 7g / L zinc sulfate, 9g / L nickel sulfate, 100ppm collagen; the current density is 30A / dm 2 , the electrodeposition time is 6s and the temperature is 40℃.

[0082] Silane spraying and drying: The copper foil was sprayed with an aqueous solution of 0.9% 3-aminopropyltriethoxysilane at 30° C.; and then dried at 220° C. for 8 seconds to obtain a blackened copper foil.

[0083] Example 2

[0084] Degreasing: The copper foil is alkaline washed with an aqueous solution of 40g / L sodium hydroxide and 18g / L sodium carbonate. The current density of the alkaline washing is 5A / dm 2 , the cleaning time is 14s, the temperature is 35℃, and the alkaline cleaning is performed twice;

[0085] Pickling: The copper foil was pickled with a 100 g / L sulfuric acid aqueous solution for 18 s at a temperature of 30 °C.

[0086] Roughening I: The pickled copper foil is placed in a roughening solution for electrodeposition treatment; wherein the roughening solution uses water as a solvent, and its components include: 110g / L sulfuric acid, 25g / L copper sulfate, and 1.0ppm chloride ion; the electrodeposition conditions are: the current density is 10A / dm 2 , the electrodeposition time was 5 s and the temperature was 25 °C;

[0087] Curing I: The roughened copper foil is placed in a curing solution for electrodeposition treatment; wherein the curing solution uses water as a solvent, and its components include: 120g / L sulfuric acid, 50g / L copper sulfate, 10ppm chloride ions, and 5ppm collagen; the electrodeposition conditions are: the current density is 35A / dm 2 , the electrodeposition time was 6 s and the temperature was 30 °C;

[0088] Repeat the above steps to perform roughening II treatment; repeat the above steps to perform curing II treatment;

[0089] Blackening: Place the cured copper foil in a blackening solution for electrodeposition. The blackening solution uses water as solvent and contains 110 g / L sulfuric acid, 30 g / L copper sulfate, 10 ppm chloride ion, 4 g / L ferrous sulfate, 6 g / L zinc sulfate, 8 g / L nickel sulfate, and 120 ppm collagen. The current density is 32 A / dm 2 , the electrodeposition time is 7s and the temperature is 35℃.

[0090] Silane spraying and drying: The copper foil was sprayed with an aqueous solution of (3-chloropropyl)trimethoxysilane at a concentration of 0.9% at 30° C.; and then dried at 240° C. for 8 seconds to obtain a blackened copper foil.

[0091] Example 3

[0092] Degreasing: The copper foil is alkaline washed with an aqueous solution of 50 g / L sodium hydroxide and 25 g / L sodium carbonate. The current density of the alkaline washing is 6 A / dm 2 , the cleaning time is 16s, the temperature is 30℃, and the alkaline cleaning is performed twice;

[0093] Pickling: The copper foil was pickled with a sulfuric acid aqueous solution with a concentration of 130 g / L, the pickling time was 15 s, and the temperature was 25 °C;

[0094] Roughening I: The pickled copper foil is placed in a roughening solution for electrodeposition treatment; wherein the roughening solution uses water as a solvent, and its components include: 120g / L sulfuric acid, 20g / L copper sulfate, and 0.8ppm chloride ion; the electrodeposition conditions are: the current density is 8A / dm 2 , the electrodeposition time was 7s and the temperature was 40°C;

[0095] Curing I: The roughened copper foil is placed in a curing solution for electrodeposition treatment; wherein the curing solution uses water as a solvent, and its components include: 130g / L sulfuric acid, 40g / L copper sulfate, 9ppm chloride ions, and 7ppm collagen; the electrodeposition conditions are: the current density is 40A / dm 2 , the electrodeposition time was 7s and the temperature was 20°C;

[0096] Repeat the above steps to perform roughening II treatment; repeat the above steps to perform curing II treatment;

[0097] Blackening: The cured copper foil is placed in a blackening solution for electrodeposition treatment; the blackening solution uses water as a solvent and its components include: 120g / L sulfuric acid, 35g / L copper sulfate, 5ppm chloride ion, 2.5g / L ferrous sulfate, 4g / L zinc sulfate, 6g / L nickel sulfate, 80ppm collagen; the current density is 28A / dm 2 , the electrodeposition time is 4s, and the temperature is 30℃.

[0098] Silane spraying and drying: The copper foil was sprayed with an aqueous solution of 1.2% aniline methyl triethoxysilane at 45° C.; and then dried at 280° C. for 6 seconds to obtain a blackened copper foil.

[0099] Example 4

[0100] Degreasing: The copper foil is alkaline washed with an aqueous solution of 45g / L sodium hydroxide and 30g / L sodium carbonate. The current density of the alkaline washing is 4A / dm 2 , the cleaning time is 18s, the temperature is 25℃, and the alkaline cleaning is performed twice;

[0101] Pickling: The copper foil was pickled with a 120 g / L sulfuric acid aqueous solution for 16 seconds at a temperature of 25°C.

[0102] Roughening I: The pickled copper foil is placed in a roughening solution for electrodeposition treatment; wherein the roughening solution uses water as a solvent, and its components include: 140g / L sulfuric acid, 10g / L copper sulfate, and 0.3ppm chloride ion; the electrodeposition conditions are: the current density is 12A / dm 2 , the electrodeposition time was 8 s and the temperature was 35 °C;

[0103] Curing I: The roughened copper foil is placed in a curing solution for electrodeposition treatment; wherein the curing solution uses water as a solvent, and its components include: 140g / L sulfuric acid, 30g / L copper sulfate, 8ppm chloride ions, and 15ppm collagen; the electrodeposition conditions are: the current density is 30A / dm 2 , the electrodeposition time was 8 s and the temperature was 40 °C;

[0104] Repeat the above steps to perform roughening II treatment; repeat the above steps to perform curing II treatment;

[0105] Blackening: The cured copper foil is placed in a blackening solution for electrodeposition treatment; the blackening solution uses water as a solvent and its components include: 140g / L sulfuric acid, 40g / L copper sulfate, 15ppm chloride ion, 3.5g / L ferrous sulfate, 5g / L zinc sulfate, 10g / L nickel sulfate, 90ppm collagen; the current density is 40A / dm 2 , the electrodeposition time is 5s and the temperature is 45℃.

[0106] Silane spraying and drying: The copper foil was sprayed with a 2% aqueous solution of 3-(isomethacryloyloxy)propyltrimethoxysilane at 40° C.; and then dried at 180° C. for 7 seconds to obtain a blackened copper foil.

[0107] Example 5

[0108] Degreasing: The copper foil is alkaline washed with an aqueous solution of 35g / L sodium hydroxide and 22g / L sodium carbonate. The current density of the alkaline washing is 5A / dm 2 , the cleaning time is 12s, the temperature is 20℃, and the alkaline cleaning is performed twice;

[0109] Pickling: The copper foil was pickled with a 150 g / L sulfuric acid aqueous solution for 12 seconds at a temperature of 20°C.

[0110] Roughening I: The pickled copper foil is placed in a roughening solution for electrodeposition treatment; wherein the roughening solution uses water as a solvent, and its components include: 130g / L sulfuric acid, 18g / L copper sulfate, and 0.9ppm chloride ion; the electrodeposition conditions are: the current density is 9A / dm 2 , the electrodeposition time was 6 s and the temperature was 35 °C;

[0111] Curing I: The roughened copper foil is placed in a curing solution for electrodeposition treatment; wherein the curing solution uses water as a solvent, and its components include: 110g / L sulfuric acid, 35g / L copper sulfate, 11ppm chloride ions, and 9ppm collagen; the electrodeposition conditions are: the current density is 32A / dm 2 , the electrodeposition time was 5 s and the temperature was 32 °C;

[0112] Repeat the above steps to perform roughening II treatment; repeat the above steps to perform curing II treatment;

[0113] Blackening: Place the cured copper foil in a blackening solution for electrodeposition treatment; the blackening solution uses water as a solvent and its components include: 100g / L sulfuric acid, 45g / L copper sulfate, 7ppm chloride ion, 3g / L ferrous sulfate, 8g / L zinc sulfate, 7g / L nickel sulfate, 95ppm collagen; the current density is 35A / dm 2 , the electrodeposition time was 8 s and the temperature was 36 °C.

[0114] Silane spraying and drying: The copper foil was sprayed with an aqueous solution of 3-glycidyloxypropyltrimethoxysilane at a concentration of 1.8% at 35° C.; and then dried at 260° C. for 6 seconds to obtain a blackened copper foil.

[0115] Example 6

[0116] The blackened copper foil was prepared in the same manner as in Example 1, except that no collagen was added during the blackening process. The other conditions remained unchanged.

[0117] Example 7

[0118] The blackened copper foil was prepared in the same manner as in Example 1, except that collagen was not added during the curing process. The other conditions remained unchanged.

[0119] Comparative Example 1

[0120] The blackened copper foil was prepared in the same manner as in Example 7, except that ferrous sulfate was not added during the blackening process. The other conditions remained unchanged.

[0121] Performance Testing

[0122] Roughness determination

[0123] According to the GB / T 1031-2009 standard method, the surface roughness of the blackened copper foils in Examples 1 to 7 and Comparative Example 1 was measured.

[0124] Determination of peel strength

[0125] According to the IPC-TM-650 standard method, the peel strength of the blackened copper foil in Examples 1 to 7 and Comparative Example 1 was measured.

[0126] Determination of oxidation performance

[0127] The blackened copper foils in Examples 1 to 7 and Comparative Example 1 were cut into 2*2 cm 2 The samples were placed in the corresponding test environment shown in Table 1 for oxidation resistance test. Before and after the test, the samples were observed under a microscope for oxidation points.

[0128] Determination of light-dark L value

[0129] Directly use a spectrophotometer to test. The Lab color model is composed of three elements: illuminance (L) and a and b related to color. L represents luminosity, which is equivalent to brightness, a represents the range from red to green, and b represents the range from blue to yellow.

[0130] Test Results

[0131] The performance tests were performed on the blackened copper foils prepared in Examples 1 to 7 and Comparative Example 1, and the corresponding test results are shown in Table 1.

[0132] Table 1 Performance test results of blackened copper foil in Examples 1 to 7 and Comparative Example 1

[0133]

[0134] The lightness L value is a method of expressing the color of the foil. The smaller the value, the darker the coating color, and the larger the brightness value, the whiter the coating color. According to Table 1, the brightness values ​​of the blackened copper foil provided by the present invention are all less than 25, which meets the requirements of blackened copper foil products.

[0135] Compared with Comparative Example 1, Examples 1 to 7 of the present invention, by adopting a blackening liquid containing ferrous sulfate, can significantly reduce the surface roughness of the copper foil while keeping the peel strength basically unchanged, thereby achieving a performance balance of high peel strength and low surface roughness of the blackened copper foil; at the same time, it can improve the oxidation resistance of the copper foil stored at 200°C.

[0136] In particular, in preferred embodiments 1-5, by using a blackening liquid with added ferrous sulfate and collagen and a curing liquid with added collagen, an excellent performance balance of low roughness (Rz≤1.2μm), high peel strength (≥1.3N / mm), and light-dark L value (black) ≤25 can be achieved. Moreover, there is no obvious oxidation point when stored at a temperature of 80°C and a humidity of 90% for 24 hours, and there is no oxidation phenomenon when stored at 200°C for 30 minutes.

[0137] The above description only relates to specific embodiments of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.

Claims

1. A blackening liquid for blackening copper foil, characterized in that: The blackening liquid contains: 100-140 g / L sulfuric acid, 25-45 g / L copper sulfate, 5-15 ppm chloride ion, 2-4 g / L ferrous sulfate, 4-8 g / L zinc sulfate and 6-10 g / L nickel sulfate.

2. The blackening liquid according to claim 1, characterized in that: The blackening liquid also includes 80 to 120 ppm of collagen.

3. The blackening liquid according to claim 1, characterized in that: The blackening liquid does not contain arsenic, lead, mercury, cobalt, cadmium and thiocyanate.

4. A surface treatment method for blackening copper foil, the method comprising the step of blackening the copper foil, characterized in that: The blackening treatment uses the blackening liquid according to any one of claims 1 to 3.

5. The method according to claim 4, characterized in that The method comprises the following steps: Step S1: degreasing the copper foil raw material to obtain degreased copper foil; Step S2: performing pickling treatment on the degreased copper foil to obtain pickled copper foil; Step S3: performing secondary roughening-curing treatment on the pickled copper foil to obtain secondary roughening-curing copper foil; the secondary roughening-curing treatment includes sequentially performing a first roughening treatment, a first curing treatment, a second roughening treatment, and a second curing treatment on the pickled copper foil; the first curing treatment and the second curing treatment include curing electrodeposition treatment using a curing liquid, and the curing liquid contains: 100-140 g / L sulfuric acid, 30-60 g / L copper sulfate, 8-12 ppm chloride ions, and 5-15 ppm collagen; Step S4: placing the secondary roughened-cured copper foil in the blackening solution for electroplating to obtain a blackened copper foil. The conditions of the electroplating treatment are: a current density of 28 to 40 A / dm 2 , electrodeposition time 4-8s, temperature 30-45°C; Step S5: performing silane coupling treatment on the blackened copper foil to obtain a copper foil product.

6. The method according to claim 5, characterized in that The degreasing treatment in step S1 includes placing the copper foil raw material in an alkaline solution for electrolytic degreasing; The alkali solution comprises: 30-50 g / L sodium hydroxide and 15-30 g / L sodium carbonate; The conditions for electrolytic degreasing are: current density 4-6A / dm 2 , temperature 20~40℃, degreasing time 12~18s; The electrolytic degreasing is preferably performed twice.

7. The method according to claim 5, characterized in that The pickling treatment in step S2 includes placing the degreased copper foil in an acid solution for pickling; The acid solution contains 100-150 g / L of sulfuric acid; The pickling conditions are: temperature 20-40° C., pickling time 12-18 s.

8. The method according to claim 5, characterized in that In step S3, The first roughening treatment comprises: placing the pickled copper foil in a roughening solution for roughening electrodeposition treatment to obtain a first roughened copper foil; The first curing treatment comprises: placing the first roughened copper foil in the curing liquid for curing electrodeposition treatment to obtain a first cured copper foil; The second roughening treatment includes: placing the first solidified copper foil in a roughening solution for roughening electrodeposition treatment to obtain a second roughened copper foil; The second curing treatment comprises: placing the second roughened copper foil in the curing liquid for curing electrodeposition treatment to obtain the secondary roughened-cured copper foil; The roughening solution contains: 100-140 g / L sulfuric acid, 10-30 g / L copper sulfate, and 0.3-1.5 ppm chloride ions; The conditions of the roughening electrodeposition treatment are: current density 8 to 12 A / dm 2 , electrodeposition time 4-8s, temperature 20-40℃; The curing electrodeposition treatment conditions are: current density 30-50A / dm 2 , electrodeposition time 4 to 8 s, temperature 20 to 40°C.

9. The method according to claim 5, characterized in that The step S5 comprises: spraying the blackened copper foil with an aqueous solution of a silane coupling agent at a temperature of 25 to 45° C., and then drying at a temperature of 180 to 280° C. for 6 to 8 seconds to obtain the copper foil product; The mass concentration of the silane coupling agent in the aqueous solution is 0.5-3%; The silane coupling agent is selected from one or more of aniline methyl triethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, glyceraldehyde propyl trimethoxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-(isomethacryloyloxy)propyl trimethoxysilane, and (3-chloropropyl) trimethoxysilane.

10. A blackened copper foil product obtained by the surface treatment method according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • Surface treatment process of copper foil for flexible copper-clad plate

    CN102618902B

  • Black surface treatment method for electrolytic copper foil

    CN105002496A

  • Black surface treatment method for rolled copper foil

    CN105603480B

  • Blackening plating solution for rolled copper foil and cyanide-free electronickelling blackening process

    CN112501659A

  • Blackening solution and cyanide-free zinc-plating cadmium-free electroplating blackening technology

    CN112609217A